COSMIC: a regimen of intensity modulated radiation therapy plus dose-escalated, raster-scanned carbon ion boost for malignant salivary gland tumors: results of the prospective phase 2 trial - Jensen, Alexandra; Nikoghosyan, Anna; Lossner, Karen; Haberer, Thomas; Jäkel, Oliver; Münter, Marc; Debus, Jürgen (International journal of radiation oncology, biology, physics, 2015)
Purpose - To investigate the effect of intensity modulated radiation therapy (IMRT) and dose-escalated carbon ion (C12) therapy in adenoid cystic carcinoma (ACC) and other malignant salivary gland tumors (MSGTs) of the head and neck. - Patients and Methods - COSMIC (combined treatment of malignant salivary gland tumors with intensity modulated radiation therapy and carbon ions) is a prospective phase 2 trial of 24 Gy(RBE) C12 followed by 50 Gy IMRT in patients with pathologically confirmed MSGT. The primary endpoint is mucositis Common Terminology Criteria grade 3; the secondary endpoints are locoregional control (LC), progression-free survival (PFS), overall survival (OS), and toxicity. Toxicity was scored according to the Common Terminology Criteria for Adverse Events version 3; treatment response was scored according to Response Evaluation Criteria in Solid Tumors 1.1. - Results - Between July 2010 and August 2011, 54 patients were accrued, and 53 were available for evaluation. The median follow-up time was 42 months; patients with microscopically incomplete resections (R1, n=20), gross residual disease (R2, n=17), and inoperable disease (n=16) were included. Eighty-nine percent of patients had ACC, and 57% had T4 tumors. The most common primary sites were paranasal sinus (34%), submandibular gland, and palate. At the completion of radiation therapy, 26% of patients experienced grade 3 mucositis, and 20 patients reported adverse events of the ear (38%). The most common observed late effects were grade 1 xerostomia (49%), hearing impairment (25%, 2% ipsilateral hearing loss), and adverse events of the eye (20%), but no visual impairment or loss of vision. Grade 1 central nervous system necrosis occurred in 6%, and 1 grade 4 ICA hemorrhage without neurologic sequelae. The best response was 54% (complete response/partial remission). At 3 years, the LC, PFS, and OS were 81.9%, 57.9%, and 78.4%, respectively. No difference was found regarding resection status. The most common site of failure was distant (55%). Local relapse was predominantly in field (79%). - Conclusion - Treatment was tolerated, with moderate acute and late toxicity. The LC at 3 years was promising. No significant difference could be shown regarding resection status; hence, extensive and mutilating surgical procedures should be rediscussed. Further dose escalation may be limited in view of potential vascular adverse events.
Gesehen am 19.06.2020